Evaluation of the functional movement screen and a novel basketball mobility test as an injury prediction tool for collegiate basketball players - Bond, C. W.; Dorman, J. C.; Odney, T. O.; Roggenbuck, S. J.; Young, S. W.; Munce, T. A. (The Journal of Strength and Conditioning Research, 2019)
Identifying injury risk and implementing preventive measures can assist in reducing injury occurrence and may ultimately improve athletic performance. Improper movement patterns often contribute to musculoskeletal (MSK) injuries. The validity of the Functional Movement Screen (FMS) as an injury prediction tool for athletes remains unclear. We designed the Basketball-Specific Mobility Test (BMT) to represent the neuromuscular demands of basketball and identify deficiencies that may be indicative of greater MSK injury risk while playing this sport. The aim of this study was to examine the association of FMS and BMT scores with injury occurrence in collegiate basketball players. We hypothesized that the BMT would be a better predictor of injury risk than the FMS, and that scores from both tests would have a higher association with severe MSK injuries than minor, non-MSK injuries. One-hundred nineteen male and female collegiate basketball players from 4 Upper Midwest universities were assessed preseason (PRE) and postseason (POST) using the FMS and BMT. In-season injury records were collected from the schools' athletic trainers and were classified by type and severity. During the season, 56 of 119 players were injured, resulting in 96 total injuries. Injured athletes' PRE FMS scores demonstrated negligible effects compared with uninjured athletes' PRE scores (d < 0.20), whereas some BMT scores showed potentially meaningful effects (d > 0.20). Although specificity of the FMS and BMT to predict injury was relatively high (FMS 85.7-87.6; BMT 42.0-88.0), sensitivity (FMS 14.2-22.7; BMT 11.6-39.1), odds ratios (FMS 1.00-2.08; BMT 0.47-1.06), and injury prediction capacities (area under the curve; FMS 0.43-0.49; BMT 0.49-0.59) of the tests were low. Although the FMS and BMT may be suitable for identifying MSK deficiencies, they do not accurately determine injury risk in collegiate basketball players. Injury risk assessments may be improved by targeting specific injury mechanisms and the conditions in which they occur.